RESPON ORANG TUA TERHADAP PEMBELAJARAN LURING SELAMA PANDEMI COVID-19 DI SMP N 2 RAO UTARA KABUPATEN PASAMAN SUMATERA BARAT - Sahra Pradisi; Yoskar Kadarisman (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
The purpose of the research is to find out of students' parents in SMPN 2 Rao Utara about Offline Learning during Pandemic Covid 19. The responses look from 3 aspects, cognitive responses, affective responses, and conative responses. Each parent surely gives a different response towards the Offline Learning system. The field survey was begun at Nagari Kotonopan village, Rao Utara sub-district, Pasaman district. To get a result of the study, the researcher used quantitative descriptive with 58 respondents. The result of the research showed parent responses to the implementation of offline learning is sufficient, either cognitive responses, affective, or conative responses. However, one of the parent responses gave a negative response because it didn’t sit well with the offline Learning implementation in SMPN 2 Rao Utara. In this way, there should need parent's engagement in Learning Implementation. Key words: response, parent, Offline Learning.